PENGARUH KOREAN WAVE TERHADAP KEPUTUSAN PEMBELIAN PADA ALBUM OFFICIAL K-POP GIRL GROUP BLACKPINK DI KABUPATEN GARUT - Rifqi Taufik rachman; Ramayani Yusuf (LP2M Universitas Perjuangan Tasikmalaya, 2023)
The purpose of this study is to measure how influential the Korean Wave variables are on purchasing decisions on the official k-pop girl group BLACKPINK's album. The method used in this study is a causal method using a quantitative approach. By taking the population in Garut Regency where there are special requirements, namely having to be a kpopers and who have listened to music or songs from BLACKPINK and taking a sample of 100 respondents. And for the validity test and reliability test this can be used in research, as well as the normality test used in research has substantial significance. The Korean Wave variable has a considerable impact on purchasing decisions, according to the direct correlation test. Based on this direct regression test, the purchasing decision variable is positively influenced by the Korean Wave variable. In addition, the Korean Wave simultaneously has a positive and significant influence on purchasing decisions, as shown by the F statistical test between the independent factors and the dependent variable. Keywords : BLACKPINK, Korean Wave, Buying Decision, K-Pop, Album Official